Use of cloth masks in the practice of infection control – evidence and policy gaps - Chughtai, Abrar Ahmad; Seale, Holly; MacIntyre, Chandini Raina (International Journal of Infection Control, 2013)
Cloth masks are commonly used in low and middle income countries. It is generally believed that the primary purpose of cloth masks is to prevent spread of infections from the wearer. However, historical evidence shows that they had been used in the past for protection of health care workers (HCWs) from respiratory infections. Currently there is a lack of evidence on the efficacy of cloth masks. In this paper, we examined the evidence on the efficacy of cloth masks and discuss the use of cloth masks as a mode of protection from infections in HCWs. We also discuss various methods to improve the effectiveness of cloth masks; for example; type of fabric, masks design and face fit. Further research is required to validate the use of cloth masks in HCWs for prevention of respiratory infections.